RETRACTED: Shaping responsible consumption patterns - Saginova Olga; Zavyalov Dmitry; Zavyalova Nadezhda (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001